Perception about the Curriculum of the School of Nursing Assistants of the Central Military Hospital (Bogotá) by their Students, Teachers, Directors and Graduates (Papeles, 2020)
One of the main challenges for job training institutions is to guarantee a pertinent and quality education. In reaching such task, the curriculum becomes a fundamental process to achieve those challenges. Hence, the main objective of this study is to know what is the perception about the curriculum by the academic community from the School of Nursing Assistants of the Central Military Hospital (Bogotá). The methodology has a quantitative approach, with a non-experimental design and is located in diagnostic studies. It was attended by 70 students, 21 graduates, 9 teachers and 2 directors of the educational center. The instrument used allows evaluating different dimensions of the curriculum, counting on internal consistency and reliability of the results obtained. The analysis of the dimensions also evaluated allows us to conclude that there is a very high consensus of perception of satisfaction among the members of the educational community of the School of Nursing Assistants of the Central Military Hospital.
Keywords: Curricular Evaluation; Nursing; Perceived Quality